PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA CYBER CRIME DI INDONESIA - Yunus Darmono (GEMA, 2023)
The field of technology is currently experiencing very rapid development and progress. It can be seen that one form of progress in the field of technology is the internet. The increasing development of the internet has had many positive impacts on its users, such as the internet making it easier to carry out long distance communications, ease of doing business, ease of obtaining information, and much more. However, apart from that, the development of the internet also has a negative impact which can lead to crime. This crime is known as cyber crime. Therefore, there is a need for legal protection for victims of cyber crime. The type of research used is library research with emphasis on sources of information from books, journals, papers and various literature. The data source used is a secondary data source.